Effect of Sea Mud Towards The Growth and Productivy of Several Varieties of Shallotin Peat Land - Azri ,; Muhammad Hatta; Wahyu Ari Nugroho (Journal of Wetlands Environmental Management, 2016)
ABSTRACTÂ Shallot cultivation in peat land was constrained by the high production costs, especially fertilizer and lime costs (Abdullah, 2011). Therefore, improvement of shallot productivity in peat land was to use local resources so that the production costs would be reduced. Potential material to be used for that purpose was sea mud which abundantly available in West Kalimantan. The productivity of several shallot varieties in peat land had not reached their production potential. The research used Randomized Block Design (RBD) with the treatment of sea mud consisted of without the treatment of sea mud (L0) and with the treatment of sea mud (L1) and several shallot varieties such as Bima Variety (V1), Manjung Variety (V2) and Sumenep Variety (V3). The research result showed that the treatment of sea mud and varieties of shallot differed significantly in improving the growth and production of shallot. Bima, Manjung and Sumenep each produced 14.73 ton/ha, 12.84 ton/ha and 9.22 ton/ha respectively. Based on profit value and B/C ratio value, the utilization of sea mud in peat land was economically feasible to be applied by farmers in West Kalimantan.Â